IDENTIFIKASI TUTUPAN TERUMBU KARANG DI PANTAI WISATA PULAU LEMUKUTAN KABUPATEN BENGKAYANG - Muhammad Azkar; Zan Zibar; Dahlia Wulan Sari (Program Studi Ilmu Kelautan, FIPAK, Universitas OSO, 2024)
The coral reef ecosystem in West Kalimantan is mostly found on the Lemukutan Island Tourism Beach, Bengkayang Regency. Lemukutan Island has an area of 1,235 Ha and has potential marine resources that can be developed and utilized by the surrounding community and the government. The aim of this research is to determine the percentage of coral cover in Surau Bay and Cina Bay. The research used the Underwater Photo Transect (UPT) method with a line transect of 50 m and a square transect measuring (58 x 44) cm². The photo shoot results were then analyzed using Coral Point Count with Excel Extensions (CPCE) computer software to obtain coral cover data and coral lifeform categories. The research results for stations 1 and 2 show Hard Coral (HC) cover of 43.80% and 35.33%. HC cover at both stations is in the medium category. The percentage of Dead Coral (DC) for stations 1 and 2 is 21.73% and 19.40%. There are several coral lifeforms in the observation area, namely Acropora Branching (ACB), Acropora Tabulate (ACT), Coral Heliopora (CHL), Coral Mushroom (CMR), Coral Encrusting (ACE), Coral Foliose (CF), and Coral Massive (CM).